Bilateral Acute Iris Transillumination - (:unkn) unknown (AMER MEDICAL ASSOC, 2011)
Objective: To describe a series of patients with bilateral acute iris transillumination, pigment dispersion, and sphincter paralysis. Methods: We reviewed the medical records and clinical photographs of 26 patients seen at 5 centers in Turkey and Belgium between March 16, 2006, and July 6, 2010. Observation procedures included clinical examination, anterior segment color photography, gonioscopy, laser flare photometry, and pupillometry. Results: All 26 patients (20 women and 6 men; mean [SD] age, 43.2 [10.5] years) had bilateral involvement. Twenty-three patients (88%) had acute-onset disease with severe photophobia and red eyes. Nineteen patients (73%) had a preceding flulike illness and used systemic antibiotics, including moxifloxacin. Diagnostic laboratory workup was unremarkable. There was pigment discharge into the anterior chamber, and flare was elevated in the absence of inflammatory cells. Most patients had severe diffuse transillumination of the iris and mydriatic distorted pupils. Pupillometry revealed a compromised reaction to light. The most serious complication was an intractable early rise in intraocular pressure. Gonioscopy revealed heavy pigment deposition in the trabecular meshwork. Although symptoms were relieved promptly by application of topical corticosteroid, the median duration of pigment dispersion was 5.25 months. Conclusions: Bilateral acute iris transillumination with pigment dispersion and persistent mydriasis is a new clinical entity that is not an ocular adverse effect of oral moxifloxacin treatment, as previously suggested. The etiopathogenesis of this entity remains to be elucidated. Arch Ophthalmol. 2011;129(10):1312-1319
Keywords: PIGMENT DISPERSION SYNDROME; UVEITIS-LIKE SYNDROME; ANTERIOR UVEITIS; ORAL MOXIFLOXACIN; CYTOMEGALOVIRUS; DEPIGMENTATION; GLAUCOMA; ATROPHY